Synthesis of PMMA/modified graphene oxide nanocomposite pour point depressant and its effect on the flow properties of Indian waxy crude oil - Sharma, R.; Mahto, V.; Vuthaluru, Hari (Elsevier Ltd, 2019)
Application of Polymeric nanocomposites as pour point depressant (PPD) for crude oil has opened the doors for a new area of research in the petroleum industry. In this research work, a polymer nanocomposite Poly(methyl methacrylate)-Graphene Oxide (PMMA-GO) was synthesized in the laboratory using in-situ free radical polymerization with varying concentrations of Graphene Oxide (0.5%, 1% PMMA), where Graphene Oxide was synthesized using Improved Hummers method and the effect of the nanocomposite on the pour point depression and rheological properties of a Indian waxy crude oil sample is observed. The synthesized nanocomposite is evaluated as pour point depressant considering the improvement in the flow properties of the crude oil. Analysis of the synthesized nanocomposites using techniques such as FTIR, Raman and UV-visible spectroscopy, Field Emission Scanning Electron Microscopy (FESEM), Gel Permeation Chromatography (GPC) revealed the formation of PMMA-Graphene Oxide and the intermediate products. Thermogravimetric analysis indicated improved thermal stability of the synthesized nanocomposite than polymer PMMA. XRD analysis confirmed the formation of graphene oxide and the resultant nanocomposite. Efficiency of the synthesized nanocomposite on the flow properties of treated crude oil is compared with the performance of a commercial PPD. Rheological properties of the crude oil treated with synthesized and commercial PPD's are compared at temperatures 30, 40 and 50 °C and better performance of the synthesized PPD is observed in terms of reduction in apparent viscosity and yield stress. Crude oil treated with PMMA-Graphene Oxide shows up to 23 °C reduction in pour point and 99.8% reduction in apparent viscosity compared with that of virgin crude oil. Reduction of gelation point of nanocomposite treated crude oil by 24 °C from virgin crude oil shows improvement in pipeline restart flow of the studied crude oil. Moreover, yield stress of the crude oil drops from 60 Pa (virgin crude oil) to 0.1 Pa for PMMA-1% Graphene Oxide treated crude oil at 1500 ppm. The reduction in gel strength of crude oil was substantiated by the microscopic analysis of virgin and PPD beneficiated crude oil. The wax crystals take more compact shape and the wax interlocking was reduced significantly in case of PMMA-1% Graphene Oxide treated crude oil. Further, the long term stability of the nanocomposite treated crude oils revealed that its rheological properties undergo lesser degradation with time, as evident by the least increase in apparent viscosity between 16.5% and 32.9% (PMMA-1% Graphene Oxide) and 28%–37.7% (PMMA-0.5% Graphene Oxide) compared to an increase of 40.175%–44.93% observed in case of commercial PPD treated crude oil. These findings show the suitability of nanocomposite PMMA-GO as pour point depressant for Indian waxy crude oil.